Waqf Based Pesantren of Education Financing - Acep Mulyadi; Nurwadjah Ahmad EQ; Muhibbin Syah; Ulfiah Ulfiah (International Journal of Nusantara Islam, 2021)
The main problem of this research is the weakness of Pesantren education funding uncertain sources of financing and standards, non-transparent financial management, and weak supervision. Waqf is one of the Islamic Shari'a which has high economic potential. there is still a gap between the potential and reality the presence of waqf has not been felt as economic benefits for mostly today's Islamic communities, including Pesantren. The conceptual framework of this research uses the concept of Elchanan Cohn, 1979; Thomas Jones, 1985; Nanang Fattah. 2012; Dedi Supriadi, 2010; Law Number 41 of 2004 concerning Waqf; Government Regulation Number 18 of 2019 concerning Pesantren; Presidential Regulation of the Republic of Indonesia Number 82 of 2021 concerning Funding for the Implementation of Pesantren; and Government Regulation No. 19 of 2007 concerning National Education Standards (SNP) The synthesis of expert opinions, laws, and government regulations, that the costs in education include direct costs and indirect costs with three financing criteria, namely investment, operational, and personal financing.The results of this study indicate that: First, waqf-based pesantren education financing is used for investment financing aspects, while operational and personal financing still needs to be developed. Second, the implementation of the waqf-based pesantren education financing program is still founded to be influencing factors, both supporting and inhibiting factors. Third, the financing of waqf-based pesantren education has an good impact on the quality of pesantren education.